(i) If k2 = μ, η = ξ + C then solution u14 we obtain $u\left(\xi \right)=-6\mu -6\mu {cot}^{2}\left(\sqrt{\mu }\left(\xi +C\right)\right)$ (i) If λ = 0, then our solutions (33) reduced to $u\left(\xi \right)=-6\mu -6\mu {cot}^{2}\left(\sqrt{\mu }\left(\xi +C\right)\right)$
(ii) If k2 = − μ, η = ξ + C then from solution u12 we obtain $u\left(\xi \right)=-6\mu +6\mu {coth}^{2}\left(\sqrt{-\mu }\left(\xi +C\right)\right)$ (ii) If λ = 0, then our solutions (28) reduced to $u\left(\xi \right)=-6\mu +6\mu {coth}^{2}\left(\sqrt{-\mu }\left(\xi +C\right)\right)$
(iii) If k = λ/2, η = ξ + C then solution u12 we obtain $u\left(\xi \right)=\frac{3}{2}{\lambda }^{2}-\frac{3}{2}{\lambda }^{2}{coth}^{2}\left(\frac{1}{2}\lambda \left(\xi +C\right)\right)$ (iii) Eq. (34) can be simplified to gives $u\left(\xi \right)=\frac{3}{2}{\lambda }^{2}-\frac{3}{2}{\lambda }^{2}{coth}^{2}\left(\frac{1}{2}\lambda \left(\xi +C\right)\right)$
(iv) If η = ξ + C + λ/2 then solution u3 we obtain $u\left(\xi \right)=-\frac{6}{{\left(\xi +C+\lambda /2\right)}^{2}}$ (iv) Eq. (35) can be simplified to gives $u\left(\xi \right)=-\frac{6}{{\left(\xi +C+\lambda /2\right)}^{2}}$ 